A prediction model to differentiate transient ischemia from irreversible transmural necrosis in closed-loop small bowel obstruction - Pan, Shaorong; Yang, Jiejin; Liu, Zining; Nai, Rile; Chen, Zeyang (Frontiers in Medicine, 2024)
The study aims to develop a prediction model to differentiate transient ischemia from irreversible transmural necrosis in closed-loop small bowel obstruction (CL-SBO).Methods: A total of 180 participants with CL-SBO between January 2010 and December 2019, of which 122 had complete radiologic data, were included to investigate the significant clinical and imaging characteristics for differentiating patients with necrosis from transient ischemia. A logistic regression model was developed and validated.In a multivariate analysis, the American Society of Anesthesiologists physical status classification system ＞2 is the independent predictor for transmural necrosis. Another multivariate analysis, including clinical and imaging factors, revealed that the imaging sign of mesenteric vessel interruption was an independent risk factor for necrosis. The diagnostic model developed using these two factors has excellent performance among the validation sets, with an area under the curve of 0.89.The diagnostic model and innovative imaging signs have substantial potential in solving this complex clinical problem.Small bowel obstruction (SBO) is one of the most common acute abdomen diseases, with